Priority areas and implementation of ecological corridor through forest restoration to safeguard biodiversity - Beltrão, Mayara Guimarães; Gonçalves, Camila Francisco; Brancalion, Pedro H. S.; Carmignotto, Ana Paula; Silveira, Luis Fábio; Galetti, Pedro Manoel; Galetti, Mauro [UNESP] (Springer Nature, 2024)
Ecological Corridors (ECs) are proposed as cost-effective solutions to improve ecological connectivity in fragmented landscapes. Planning the implementation of ECs must take into account landscape features as they affect the viability of the endeavor and the ECs associated costs. A novel set of geoprocessing tools were used to assess (i) economic viability; (ii) socioeconomic cost-effectiveness; and (iii) to determine priority targets for ECs establishment in a highly fragmented region of Atlantic Forest. Landscape features (e.g. size, edge density, number of patches), land use and cover, and Enhanced Vegetation Index data were obtained from remote sensing. Composition and configuration landscape metrics were estimated by geostatistical methods. Study area was represented by 35,344 forest fragments, of which 94% were composed of fragments smaller than 10 hectares in size, leading to a landscape characterized by low connectivity. We identified 13 priority fragments for protection and propose five ecological corridors. These five ECs connect six priority fragments, with a total of 283.93 ha of area to restore, on an estimated cost of nearly US$550.000,00. Conserving the biodiversity of one of the most threatened and fragmented tropical rainforest regions could be promoted at modest costs, through the protection of key fragments and their reconnection in the landscape.
Keywords: Atlantic Forest; Enhanced Vegetation Index; Forest cover; Forest restoration; Functional connectivity; Pernambuco Endemism Center